Don't Panic with Mechanics! Fun and success in the "loser discipline" of engineering studies! - Romberg, Oliver; Hinrichs, Nikolaus; SpringerLink (Online service) (Wiesbaden : Vieweg+Teubner Verlag : Imprint: Vieweg+Teubner Verlag, 2006)
The ultimate companion in the classical horror discipline of engineering science! Contents of the book are the basics of mechanics as treated in engineering and physical sciences: Statics, Elastostatics, Kinematics & Kinetics in unconventional, humorous presentation with many cartoons, funny explanations and a chapter containing several exercises with detailed solutions.
In Full Possession of Our Mental Forces And Moments: Statics -- Enough Rigid Thinking: Elastostatics -- Everything in Motion: Kinematics and Kinetics -- Practice Makes the Loser a Winner.
Keywords: Mechanics; Mechanics, Applied; Physics; Mechanical engineering; Theoretical and Applied Mechanics; Physics, general; Mechanical Engineering